2016
DOI: 10.1007/s13139-016-0439-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Androgen Deprivation Therapy on the Uptake of PSMA-Targeted Agents: Emerging Opportunities and Challenges

Abstract: Prostate-specific membrane antigen (PSMA) is an attractive target for both diagnosis and therapy because of its high expression in the vast majority of prostate cancers. Development of small molecules for targeting PSMA is important for molecular imaging and radionuclide therapy of prostate cancer. Recent evidence implies that androgen-deprivation therapy increase PSMA-ligand uptake in some cases. The reported upregulations in PSMA-ligand uptake after exposure to second-generation antiandrogens such as enzalut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 63 publications
1
39
0
Order By: Relevance
“…It has already been demonstrated that in both androgensensitive and androgen-resistant human prostate adenocarcinoma cells (LNCaP), the expression of PSMA is upregulated post-ADT and downregulated in the presence of testosterone or DHT [14][15][16]. Although a case report published by Hope et al corroborated these preclinical studies, demonstrating a 7fold increase in PSMA SUVmax values after the initiation of ADT, our results are in line with the two very recently published studies [10][11][12].…”
Section: Discussionsupporting
confidence: 92%
“…It has already been demonstrated that in both androgensensitive and androgen-resistant human prostate adenocarcinoma cells (LNCaP), the expression of PSMA is upregulated post-ADT and downregulated in the presence of testosterone or DHT [14][15][16]. Although a case report published by Hope et al corroborated these preclinical studies, demonstrating a 7fold increase in PSMA SUVmax values after the initiation of ADT, our results are in line with the two very recently published studies [10][11][12].…”
Section: Discussionsupporting
confidence: 92%
“…Recent data suggests that androgen deprivation therapy increases PSMA expression under certain circumstances. 19 Thus, upregulation of PSMA expression following androgen withdrawal has already been described in 1996 by Wright et al 20 In addition, Meller et al 9 revealed an increased PSMA expression following short-term treatment of prostate cancer cells with abiraterone. Further investigations suggested a timedependent effect of AR inhibition using enzalutamide on PSMA expression in vitro.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, the antitumor activity of 177 Lu‐PSMA‐617 radioligand therapy might be improved after inducing PSMA expression. Recent data suggests that androgen deprivation therapy increases PSMA expression under certain circumstances . Thus, upregulation of PSMA expression following androgen withdrawal has already been described in 1996 by Wright et al In addition, Meller et al revealed an increased PSMA expression following short‐term treatment of prostate cancer cells with abiraterone.…”
Section: Discussionmentioning
confidence: 87%
“…Clinical reports show the possibility of a false-positive uptake of PSMA-targeted radioligand after ARPI (Hope et al 2017) and a false-negative uptake of this radioligand in NEPC (Chakraborty et al 2015, Tosoian et al 2017, Usmani et al 2017. We previously reviewed the available preclinical evidence justifying molecular backgrounds of a false-positive uptake of PSMA-targeted radioligand after ARPI (Bakht et al 2017). However, there is a lack of preclinical evidence for the reported false-negative uptake of PSMA-targeted radioligand.…”
Section: Discussionmentioning
confidence: 99%